Living Well to Keep Your Pressure Down - Linda B. Bobroff (EDIS)
High blood pressure, or hypertension, can cause serious health problems. It makes your heart work harder and can damage your blood vessels even if you feel okay. Everyone should have their blood pressure checked regularly. If you have certain risk factors, you are more likely to have high blood pressure. Follow these recommendations to help reduce your risk for high blood pressure. This 6-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, January 2013.